Advance in the application of organoids in bone diseases - Kong, Yajie; Yang, Yujia; Hou, Yu; Wang, Yuzhong; Li, Wenjing; Song, Yongzhou (Frontiers in Cell and Developmental Biology, 2024)
Bone diseases such as osteoporosis and osteoarthritis have become important human health problems, requiring a deeper understanding of the pathogenesis of related diseases and the development of more effective treatments. Bone organoids are threedimensional tissue masses that are useful for drug screening, regenerative medicine, and disease modeling because they may mimic the structure and physiological activities of organs. Here, we describe various potential methods for culturing bone-related organoids from different stem cells, detailing the construction processes and highlighting the main applications of these bone organoid models. The application of bone organoids in different skeletal diseases is highlighted, and current and promising bone organoids for drug screening and regenerative medicine as well as the latest technological advancements in bone organoids are discussed, while the future development of bone organoids is discussed. Looking forward, it will provide a reference for constructing bone organoids with more complete structures and functions and applying them to biomedical research.